HUBUNGAN SOFA SCORE DENGAN MORTALITAS PASIEN SEPSIS DI UNIT PERAWATAN INTENSIF COVID RSPAD GATOT SOEBROTO TAHUN 2021 - Aryadhira Parameswari (2023)
Coronavirus Disease-2019 (COVID-19) caused by SARS-CoV-2 was first identified in Wuhan, China, is an infectious disease that causes problems worldwide and has spread to various countries. COVID-19 in severe cases can develop into sepsis and organ dysfunction, which is caused by a dysregulation of the body's immune response to infection. Organ dysfunction is indicated by an increase in the Sequential (sepsis-related) Organ Failure Assessment (SOFA) Score. The aim of the study was to investigate the relationship between the SOFA Score and the mortality of sepsis patients in the Covid Intensive Care Unit of Indonesian Army Central Hospital Gatot Soebroto in 2021. This study used a cross-sectional method with an observational analytic design. The sampling technique uses total sampling and Fisher's test. The results of the study obtained 53 samples of sepsis patients with COVID-19 which showed that 94.3% of sepsis patients with COVID-19 died and 5.7% were alive. Bivariate analysis with Fisher's test showed p > 0.05, which was 1.000. The conclusion of the study showed that the SOFA Score was not significantly related to the mortality of sepsis patients in the COVID-19 Intensive Care Unit.